A meta-analysis on the impact of grades and comments on academic motivation and achievement: a case for written feedback. Issue 7 (9th August 2021) - Koenka, Alison C.; Linnenbrink-Garcia, Lisa; Moshontz, Hannah; Atkinson, Kayla M.; Sanchez, Carmen E.; Cooper, Harris
Abstract: This research synthesis examined the impact of grades, comments, and no performance feedback on academic motivation and achievement in elementary and secondary school. Four meta-analyses were conducted, with two each exploring the impact of (a) grades versus no performance feedback and (b) grades versus comments on academic motivation and achievement, respectively. Overall results indicated that grades positively influenced achievement but negatively influenced motivation compared to no feedback. However, compared to those who received comments, students receiving grades had poorer achievement and less optimal motivation. Moderator analyses generally suggested that overall effects varied as a function of the type of motivation (i.e. the specific construct, internal vs. external motivation), context (e.g. academic subject; comment type), student characteristics (e.g. achievement level), and methodology (i.e. grade anticipation versus receipt), though it was not possible to test these moderators in all analyses. Theoretical and methodological contributions and implications for education practice are discussed.